2011
DOI: 10.1007/s00394-011-0238-8
|View full text |Cite
|
Sign up to set email alerts
|

Short-term supplementation with Aronia melanocarpa extract improves platelet aggregation, clotting, and fibrinolysis in patients with metabolic syndrome

Abstract: PurposeA diet rich in berries is believed to play a distinct role in the prevention of metabolic diseases associated with obesity. So far, there have been no published clinical observations evaluating the influence of Aronia melanocarpa on hemostasis. The aim of our study was to investigate the effects of A. melanocarpa extract (AM) supplementation on platelet aggregation, clot formation, and lysis in patients with metabolic syndrome (MS).MethodsMiddle-aged non-medicated subjects with MS (n = 38) and 14 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 19 publications
1
57
0
Order By: Relevance
“…Seven studies used the product Aronox R (Agropharm Ltd, Poland), which contained 15 mg of anthocyanins in a 100-mg tablet at a daily dose of three tablets (300 mg) per day-giving a daily dose of 45 mg of anthocyanins . A later exploratory study in patients suffering from metabolic syndrome investigated a daily dose of 300 mg of chokeberry extract, giving a daily dose of 80 mg of the total polyphenols that included at least 60 mg of anthocyanins (Sikora et al, 2012): this confirmed that blood lipids significantly decreased over 2 months of treatment. Beneficial changes in coagulation indices (reduction in adenosine diphosphate-induced clot formation and inhibition of the amidolytic activities of both thrombin and plasmin) were also observed (Sikora et al, 2012;Sikora et al, 2014a).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Seven studies used the product Aronox R (Agropharm Ltd, Poland), which contained 15 mg of anthocyanins in a 100-mg tablet at a daily dose of three tablets (300 mg) per day-giving a daily dose of 45 mg of anthocyanins . A later exploratory study in patients suffering from metabolic syndrome investigated a daily dose of 300 mg of chokeberry extract, giving a daily dose of 80 mg of the total polyphenols that included at least 60 mg of anthocyanins (Sikora et al, 2012): this confirmed that blood lipids significantly decreased over 2 months of treatment. Beneficial changes in coagulation indices (reduction in adenosine diphosphate-induced clot formation and inhibition of the amidolytic activities of both thrombin and plasmin) were also observed (Sikora et al, 2012;Sikora et al, 2014a).…”
Section: Discussionmentioning
confidence: 88%
“…A later exploratory study in patients suffering from metabolic syndrome investigated a daily dose of 300 mg of chokeberry extract, giving a daily dose of 80 mg of the total polyphenols that included at least 60 mg of anthocyanins (Sikora et al ., ): this confirmed that blood lipids significantly decreased over 2 months of treatment. Beneficial changes in coagulation indices (reduction in adenosine diphosphate‐induced clot formation and inhibition of the amidolytic activities of both thrombin and plasmin) were also observed (Sikora et al ., ; Sikora et al ., ). In accordance with this, an improvement of the rheological properties of erythrocytes was shown in hypercholesterolemic patients receiving 300‐mg Aronox R over 2 months (Duchnowicz et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Serum triglycerides were also significantly decreased, as well as parameters of platelet aggregation and coagulation [45]. …”
Section: Chokeberrymentioning
confidence: 99%
“…In another study, Sikora et al . () investigated the effects of A . melanocarpa extract supplementation on platelet aggregation, clot formation, and lysis in patients with metabolic syndrome.…”
Section: Antiplatelet Properties Of Medicinal Plants: Bioactive Constmentioning
confidence: 99%